Factors Associated with the Occurrence of Hypertension in Bonegunu Public Health Centers, North Buton Regency - Astuti, Fitri Diana; Marsia, Marsia; Juliana, Nur; Sari, Maya; Rohmawati, Wahidah (MALATA SAINS INDONESIA, 2024)
Introduction: Hypertension is a major public health problem and is ranked fourth in the world based on its prevalence. Hypertension often occurs due to several factors, namely age, education, work, family history, obesity, exercise habits, and so on. Objectives: The aim of this study was to determine the relationship between age, occupation, and diet on the incidence of hypertension in the Bonegunu Community Health Center working area, North Buton Regency. Methods: This type of analytical observational research with a Cross-Sectional Study design. The sampling technique used purposive sampling with a sample size of 38 people. The research instruments were a questionnaire and Frequency Questionnaire Form sheet as well as a 24-hour Food Recall Form. Data analysis was carried out univariately and bivariately using the chi-square statistical test (significant if the p-value <0.05). Results: The research results showed that age and the incidence of hypertension p value = 0.000 < α = 0.05, which means there is a relationship between age and the incidence of hypertension. Occupation and the incidence of hypertension p value = 0.002 < α = 0.05, which means there is a relationship between employment and the incidence of hypertension. Dietary patterns and the incidence of hypertension p value = 0.007 < α = 0.05, which means there is a relationship between dietary patterns and the incidence of hypertension. Conclusion: There is a need for education through regular health promotions to the community or through monthly posbindu activities for early detection.